Measurement Invariance of Torrance Test of Creative Thinking Figural Scores across Age: A study in Spanish-Speaking Children and Adolescents. - Gabriela L. Krumm; Vanessa Arán Filippetti; María Aranguren; Viviana Lemos; Jael Vargas Rubilar (CAEN, 2013)
On the basis of a previous study carried out with Spanish-speaking children which indicates that the Creativity construct, operationalized by means of the Torrance Tests of Creative Thinking (TTCT)-Figural, consists of two factors -Innovation and Adaptation- (Krumm, Lemos & Arán Filippetti, in press), the objective of the present work was to prove whether this structure is invariant across age. A sample of 652 Spanish-speaking children and adolescents aged 9-17 years of both sexes was tested. It was in turn divided into three age groups: (a) 9-10, (b) 11-13 and (c) 16 -17 years. Confirmatory Factor Analysis (CFA) showed that in each group of the sample, the structure of the TTCT is composed of two correlated factors, namely Innovation and Adaptation. In addition, Multigroup CFA demonstrated that the two-factor solution was actually invariant (configural and metric) across age, meaning that children and adolescents equally conceptualize the Creativity construct. Finally, MANOVA showed a significant age effect on every subscale. These data suggest the relevance of considering the age factor when assessing the creative potential through the TTCT-Figural.